2023
DOI: 10.1007/s00167-023-07457-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of return to sport and functional outcomes following distal femoral, double level and high tibial osteotomies for active patients with symptomatic varus malalignment

Abstract: Purpose This study indicated the outcomes of three surgical techniques for the treatment of symptomatic unicompartmental knee osteoarthritis (UKOA) with varus malalignment in younger, active patients: distal femoral osteotomy (DFO), doublelevel osteotomy (DLO) and high tibial osteotomy (HTO). The outcomes measured included the return to sport, sport activity and functional scores. Methods A total of 103 patients (19 DFO, 43 DLO, 41 HTO) were enrolled in the study and were divided into three groups based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Minzlaf et al [31] reported that young active patients were able to return to the preoperative sports activity level 1 year after undergoing osteochondral autologous transplantation with OWHTO for valgus defect. More recent studies have shown similar findings, including 87%-94% of patients returning to sports and work, with 78%-85% returning to their presymptomatic sports level after knee osteotomies [1,19,26]. However, the rate of return to sports after MMPRT repair in patients who underwent OWHTO has not been reported.…”
Section: Discussionmentioning
confidence: 67%
“…Minzlaf et al [31] reported that young active patients were able to return to the preoperative sports activity level 1 year after undergoing osteochondral autologous transplantation with OWHTO for valgus defect. More recent studies have shown similar findings, including 87%-94% of patients returning to sports and work, with 78%-85% returning to their presymptomatic sports level after knee osteotomies [1,19,26]. However, the rate of return to sports after MMPRT repair in patients who underwent OWHTO has not been reported.…”
Section: Discussionmentioning
confidence: 67%
“…However, in cases of substantial or bifocal deformities, a single‐level osteotomy may significantly increase the joint line obliquity (JLO) with resultant tibiofemoral subluxation, pressure distribution changes and excessive shear stresses on the articular cartilage [ 2 , 34 , 37 , 54 ]. In such cases, DLO is gaining popularity over single‐level knee osteotomy due to its merits in maintaining a more physiologic joint alignment and orientation with better clinical results [ 1 , 7 , 47 ] and comparable return to sports [ 6 , 12 ]. Nevertheless, DLO is a complex procedure, and accuracy is of the essence.…”
Section: Introductionmentioning
confidence: 99%